The Impact of Antiplatelet Treatment on Endothelial Function - Androulakis, Emmanuel; Norrington, Karl; Bakogiannis, Constantinos; Lioudaki, Eirini; Siasos, Gerasimos; Tousoulis, Dimitris (Current Pharmaceutical Design, 2016)
The vascular endothelium comprises a continuous single cell layer of endothelial cells which line the entire cardiovascular system. Impaired endothelial function underlies the pathogenesis and contributes to the progression of atherosclerosis. Oxidative stress, vasoconstriction, inflammation, proliferation and thrombosis occur in dysfunctional endothelium while the latter, is primarily mediated by platelet activation and adherence to vascular wall. Despite the primary action of antiplatelet agents including aspirin, P2Y12 ADP receptor antagonists and glycoprotein IIb/IIIa inhibitors, a growing body of literature suggests that an important mechanism of their action involves complex modulation of endothelial function via platelet-endothelial interactions, modification of the inflammatory cytokine cascade and nitric oxide mediated effects. These agents represent the mainstay in pharmacological treatment of all aspects of cardiovascular disease both in primary and secondary prevention. However beyond these properties, it is important to note that pharmacological modification of endothelial dysfunction has been postulated as a therapeutic target for reduction of cardiovascular events.
Keywords: antiplatelets